The Dilemma Of Operationalizing The Enterprise Under UNCLOS 1982 - Agustina Merdekawati; Marsudi Triatmodjo; I Made Andi Arsana; Hasibuan, Irkham Afnan Trisandi (Faculty of Law, Universitas Brawijaya, 2023)
The Area's deep-seabed mining activities require substantial capital and sophisticated technologies, which become barriers for developing countries. UNCLOS 1982 envisioned that the presence of the Enterprise would solve this problem. However, the Enterprise is yet to be operationalized. The UNCLOS 1982’s Implementing Agreement 1994 postponed the Enterprise’s independent operation until the requirement is fulfilled. However, there have been changes within the international community that might affect the urgency on the Enterprise’s operationalization. This paper explored the dilemma of the Enterprise’s operationalization in ensuring the participation of developing countries and to generate the optimum benefits to all mankind. This research is aimed to contribute to the understanding of contemporary problems in applying the common heritage of mankind principle in the Area. The research found three dilemmas: (a) divided interests of developing countries; (b) optimizing financial benefits redistribution; and (c) the diminishing role attributed to the Enterprise. The research concluded that it is necessary to review the provisions in UNCLOS 1982 and the 1994 Agreement with the spirit of ensuring the participation of developing countries in the Area utilization by adjusting to the current situation of the international community.